Molecular reassessment of diaporthalean fungi associated with strawberry, including the leaf blight fungus, Paraphomopsis obscurans gen. et comb. nov. (Melanconiellaceae) - Dhanushka Udayanga; Shaneya D. Miriyagalla; Dimuthu S. Manamgoda; Kim S. Lewers; Alain Gardiennet; Lisa A. Castlebury (IMA Fungus)
ABSTRACT Phytopathogenic fungi in the order Diaporthales (Sordariomycetes) cause diseases on numerous economically important crops worldwide. In this study, we reassessed the diaporthalean species associated with prominent diseases of strawberry, namely leaf blight, leaf blotch, root rot and petiole blight, based on molecular data and morphological characters using fresh and herbarium collections. Combined analyses of four nuclear loci, 28S ribosomal DNA/large subunit rDNA (LSU), ribosomal internal transcribed spacers 1 and 2 with 5.8S ribosomal DNA (ITS), partial sequences of second largest subunit of RNA polymerase II (RPB2) and translation elongation factor 1-α (TEF1), were used to reconstruct a phylogeny for these pathogens. Results confirmed that the leaf blight pathogen formerly known as Phomopsis obscurans belongs in the family Melanconiellaceae and not with Diaporthe (syn. Phomopsis) or any other known genus in the order. A new genus Paraphomopsis is introduced herein with a new combination, Paraphomopsis obscurans, to accommodate the leaf blight fungus. Gnomoniopsis fragariae comb. nov. (Gnomoniaceae), is introduced to accommodate Gnomoniopsis fructicola, the cause of leaf blotch of strawberry. Both of the fungi causing leaf blight and leaf blotch were epitypified. Fresh collections and new molecular data were incorporated for Paragnomonia fragariae (Sydowiellaceae), which causes petiole blight and root rot of strawberry and is distinct from the above taxa. An updated multilocus phylogeny for the Diaporthales is provided with representatives of currently known families.